Mathématiques
Befen
1

1. Factorise 4x²-9 2.Déduis-en une factorisation de l'expression : 4x-9+(2x+3)(x-1)

+0
(2) Réponses
boudax93

Bonsoir, 1) 4x² - 9 = (2x)² - 3² = (2x + 3)(2x - 3) 2) Donc  4x² - 9 + (2x+3)(x-1) = (2x+3)(2x-3)+(2x+3)(x-1) = (2x+3)(2x - 3 + x - 1) = (2x + 3)(3x - 4)

cacahuette

4x² - 9             a² - b² = (a + b )(a - b) (2x)² - 3² (2x + 3)(2x - 3) 2)  4x² - 9 + (2x + 3)(x - 1)      (2x - 3)(2x + 3) +(2x + 3)(x - 1)       (2x + 3) (2x - 3 + x - 1)      (2x + 3)(3x - 4)

Ajouter une réponse